Unmet Rehabilitation Needs after Traumatic Brain Injury across Europe: Results from the CENTER-TBI Study - Andelic Nada; Roe Cecilie; Tenovuo Olli; Azouvi Philippe; Dawes Helen; Majdan Marek; Ranta Jukka; Howe Emilie I; Wiegers Eveline JA; Tverdal Cathrine; Borgen Ida; Forslund Marit V; et al. (MDPI, 2022)
This study aims to assess rehabilitation needs and provision of rehabilitation services for individuals with moderate-to-severe disability and investigate factors influencing the probability of receiving rehabilitation within six months after traumatic brain injury (TBI). Overall, the analyses included 1206 individuals enrolled in the CENTER-TBI study with severe-to-moderate disability. Impairments in five outcome domains (daily life activities, physical, cognition, speech/language, and psychological) and the use of respective rehabilitation services (occupational therapy, physiotherapy, cognitive and speech therapies, and psychological counselling) were recorded. Sociodemographic and injury-related factors were used to investigate the probability of receiving rehabilitation. Physiotherapy was the most frequently provided rehabilitation service, followed by speech and occupational therapy. Psychological counselling was the least frequently accessed service. The probability of receiving a rehabilitative intervention increased for individuals with greater brain injury severity (odds ratio (OR) 1.75, CI 95%: 1.27-2.42), physical (OR 1.92, CI 95%: 1.21-3.05) and cognitive problems (OR 4.00, CI 95%: 2.34-6.83) but decreased for individuals reporting psychological problems (OR 0.57, CI 95%: 1.21-3.05). The study results emphasize the need for more extensive prescription of rehabilitation services for individuals with disability. Moreover, targeted rehabilitation programs, which aim to improve outcomes, should specifically involve psychological services to meet the needs of individuals recovering from TBI.